Roughage Sources During Late Gestation and Lactation Alter Metabolism, Immune Function and Rumen Microbiota in Ewes and Their Offsprings - Haidong Du; Kenan Li; Wenliang Guo; Meila Na; Jing Zhang; Renhua Na (Microorganisms)
Maternal metabolic intensity significantly increases during late gestation and lactation, placing significant stress on cells and tissues. This heightened metabolic demand can lead to inflammatory responses and metabolic disorders, adversely affecting the health of both the mother and her offspring. Diet plays a key role in modulating host health by influencing the gastrointestinal microbiome. This study examined the impact of two roughage sources, corn straw (CS), and alfalfa hay (AH), on ewes and their offspring during late gestation and lactation, with a focus on metabolism, immunity, and the microbiome. Thirty-six multiparous Inner Mongolia cashmere goats, approximately 60 days pregnant, were assigned to CS and AH groups. Samples were collected from the ewes on day 140 of gestation (G140) and day 28 of lactation (L28) for analysis. The results showed that ewes fed AH had reduced body weight loss during lactation (p < 0.05), and increased serum metabolic factors levels (p < 0.05). Additionally, ewes in the AH group exhibited a reduced inflammatory response during both gestation and lactation compared to those in the CS group, as evidenced by a significant decrease in TNF-α and LPS levels and a notable increase in IL-10 (p < 0.05). The rumen microbiomes of ewes in the AH and CS groups exhibited stark differences, with specific microbial markers identified at G140 and L28. Correlation analysis revealed associations between microbiome, volatile fatty acids, cytokines, and metabolic markers. The analysis of the lambs demonstrated that their immune status and microbial composition were significantly influenced by the immune health and microbial community structure of the ewe. Moreover, microbial and immune-related components from the ewes were transmitted to the lambs, further shaping their immune development and rumen microbiota. Overall, different roughage sources during late gestation and lactation had minimal impact on the growth performance of ewes and lambs, given that both diets were iso-nitrogen and iso-energetic. However, ewes fed AH exhibited significant improvements in immune function and overall health for both them and their lambs.